Green Shipping Management - Lun, Y.H. Venus; Lai, Kee-hung.; Wong, Christina W.Y.; Cheng, T. C. E.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2016)
This book presents theory-driven discussion on the link between implementing green shipping practices (GSP) and shipping firm performance. It examines the shipping industry's challenge of supporting economic growth while enhancing environmental performance. Consisting of nine chapters, the book covers topics such as the conceptualization of green shipping practices (GSPs), measurement scales for evaluating GSP implementation, greening capability, greening and performance relativity (GPR), green management practice, green shipping network, greening capacity, and greening propensity. In view of the increasing quest for environment protection in the shipping sector, this book provides a good reference for firms to understand and evaluate their capability in carrying out green operations on their shipping activities.
Normal 0 false false false EN-US X-NONE X-NONE MicrosoftInternetExplorer4 Introduction to Green Shipping Practices -- Adoption of Green Shipping Practices -- Measures for Evaluating Green Shipping Practices -- Green Management Practices -- Development of a Green Shipping Network -- Evaluation of Green Shipping Networks -- Shipping Operations and Green Capability -- Relativity between Greening and Performance -- Greening Propensity. /* Style Definitions*/ table.MsoNormalTable {mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-qformat:yes; mso-style-parent:""; mso-padding-alt:0in 5.4pt 0in 5.4pt; mso-para-margin-top:0in; mso-para-margin-right:0in; mso-para-margin-bottom:10.0pt; mso-para-margin-left:0in; line-height:115%; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-fareast-font-family:"Times New Roman"; mso-fareast-theme-font:minor-fareast; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin; mso-bidi-font-family:"Times New Roman"; mso-bidi-theme-font:minor-bidi;}.
Keywords: Transportation engineering; Traffic engineering; Renewable energy sources; Environmental engineering; Biotechnology; Bioremediation; Transportation Technology and Traffic Engineering; Renewable Energy; Environmental Engineering/Biotechnology.